Occurrence of a Mosaic Virus in Guava - Sidek, Zakaria; Lim, Tong Kwee (1990)
Leaves from a shoot of guava cv. Burma Red were found to exhibit mosaic symptoms typical of a virus disease. Transmission electron microscopic studies of the sap from infected leaves revealed an isometric virus particle with a diameter of58-64 nm. The virus can be transmitted mechanically from cv. Burma Red to cv. Kampuchea seedlings. Based on the symptom, the virus can be tentatively designated as guava mosaic virus.